Development of a model for temperature in a grinding mill - Kapakyulu, Edgar (My University, 2008)
Abstract Grinding mills are generally very inefficient, difficult to control and costly, in terms of both power and steel consumption. Improved understanding of temperature behaviour in milling circuits can be used in the model-based control of milling circuits. The loss of energy to the environment from the grinding mill is significant hence the need for adequate modeling. The main objectives of this work are to quantify the various rates of energy loss from the grinding mill so that a reliable model for temperature behaviour in a mill could be developed. Firstly models of temperature behaviour in a grinding mill are developed followed by the development of a model for the overall heat transfer coefficient for the grinding mill as a function of the load volume, mill speed and the design of the liners and mill shell using the energy balances in order to model energy loss from the mill. The energy loss via convection through the mill shell is accounted for by quantifying the overall heat transfer coefficient of the shell. Batch tests with balls only were conducted. The practical aspect of the work involved the measurement of the temperatures of the mill load, air above the load, the liners, mill shell and the environmental temperature. Other measurements were: mill power and sound energy from the mill. Energy balances are performed around the entire mill. A model that can predict the overall heat transfer coefficient over a broad range of operating conditions was obtained. It was found that the overall heat transfer coefficient for the grinding mill is a function of the individual heat transfer coefficients inside the mill and outside the mill shell as well as the design of the liners and shell. It was also found that inside heat transfer coefficients are affected by the load volume and mill speed. The external heat transfer coefficient is affected by the speed of the mill. The values for the overall heat transfer coefficient obtained in this work ranged from 14.4 – 21W/m2K. iv List of Publications The author has published the following papers based on the contents of this dissertation as follows: Published conference abstract Kapakyulu, E., and Moys, M.H., 2005. Modelling of energy loss to the environment from the grinding mill, Proceedings of the Mineral Processing 2005’ Conference, SAIMM, Cape Town, South Africa, 4-5 Aug. pp 65-66 - SP03 Research Papers: Accepted for publication and currently in press in Minerals Engineering: Kapakyulu, E., and Moys, M.H., 2006. Modelling of energy loss to the environment from a grinding mill, Part I: Motivation, Literature Survey and Pilot Plant Measurements, (Currently in press in Minerals Engineering) Kapakyulu, E., and Moys, M.H., 2006. Modelling of energy loss to the environment from a grinding mill, Part II: Modeling the overall heat transfer coefficient, (Currently in press in Minerals Engineering)
Keywords: grinding modelling; temperature